Implementasi Sistem Informasi E-Booking Lapangan Bulu Tangkis di GOR Kemayoran Berbasis Web - Sutisna, Sutisna; Adnan, Kemal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The advancement of information technology is currently encouraging various service sectors to adapt, including in the management of sports facilities. GOR Kemayoran faces problems in the badminton court booking system which is still done manually, leading to irregular schedules, recording errors, and inconvenience for users. This study aims to design and implement a website-based badminton court e-booking information system that can simplify the booking process for the public and increase the efficiency of managing the field schedule at GOR Kemayoran. The method used in this study is the waterfall development model, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The result is a web-based e-booking application that provides online booking features and schedule availability checks. It is expected that this system will provide convenience for customers in making reservations and assist management in arranging schedules and recording transactions more effectively and in a structured manner.